The Quality of Life in Asia A Comparison of Quality of Life in Asia - Inoguchi, Takashi; Fujii, Seiji; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
This book comprehensively and systematically explores demographic profile, lifestyles, value priorities, and subjective and objective quality of life of the ordinary citizens in most societies in Asia, utilizing the AsiaBarometer Surveys conducted annually from 2003 through 2008. The surveyed area encompasses 29 societies in East, Southeast, South and Central Asia. The book examines life quality in each individual society and compares it between societies. In addition, the book studies generalized characteristics of life quality in the entire and sub-regions of Asia. This book is intended for scholars in the fields of quality of life, political science, sociology and economics as well as for policymakers.
Table of content- 1. Introduction -- 2. Quality of Life in Twenty-nine Societies in Asia -- 3. Comparison of Quality of Life between Societies -- 4. Key Characteristics of Quality of Life in Asia and its Sub-regions: East, Southeast, South, and Central Asia -- 5. Conclusion.
Keywords: Social sciences; Quality of Life; Regional economics; Social policy; Quality of Life -- Research; Social Sciences; Quality of Life Research; Social Policy; Political Science, general; Regional/Spatial Science; Social Sciences, general